Laboratory Diagnosis of Invasive Aspergillosis: From Diagnosis to Prediction of Outcome - Richard C. Barton (Scientifica)
Invasive aspergillosis (IA), an infection caused by fungi in the genus Aspergillus, is seen in patients with immunological deficits, particularly acute leukaemia and stem cell transplantation, and has been associated with high rates of mortality in previous years. Diagnosing IA has long been problematic owing to the inability to culture the main causal agent A. fumigatus from blood. Microscopic examination and culture of respiratory tract specimens have lacked sensitivity, and biopsy tissue for histopathological examination is rarely obtainable. Thus, for many years there has been a great interest in nonculture-based techniques such as the detection of galactomannan, β-D-glucan, and DNA by PCR-based methods. Recent meta-analyses suggest that these approaches have broadly similar performance parameters in terms of sensitivity and specificity to diagnose IA. Improvements have been made in our understanding of the limitations of antigen assays and the standardisation of PCR-based DNA detection. Thus, in more recent years, the debate has focussed on how these assays can be incorporated into diagnostic strategies to maximise improvements in outcome whilst limiting unnecessary use of antifungal therapy. Furthermore, there is a current interest in applying these tests to monitor the effectiveness of therapy after diagnosis and predict clinical outcomes. The search for improved markers for the early and sensitive diagnosis of IA continues to be a challenge.